THE HISTORY AND NATURE OF THE INVESTIGATIVE INTERVIEWING OF SUSPECTS (World Bulletin of Management and Law, 2024)
This article highlights the essence, types, characteristics and evolutionary development of interrogation of suspects in the world history and the history of Uzbekistan, at the same time, the author’s definition of the concepts of interrogation of the suspect and tactics of the suspect is given in the article.